If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(g + -84) = 72 Reorder the terms: 9(-84 + g) = 72 (-84 * 9 + g * 9) = 72 (-756 + 9g) = 72 Solving -756 + 9g = 72 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '756' to each side of the equation. -756 + 756 + 9g = 72 + 756 Combine like terms: -756 + 756 = 0 0 + 9g = 72 + 756 9g = 72 + 756 Combine like terms: 72 + 756 = 828 9g = 828 Divide each side by '9'. g = 92 Simplifying g = 92
| X^3=14000 | | 2(x-2)-5=3(x-7) | | X=14-6x | | 85=-3(u+26)+13 | | 5x+1=6x+2 | | abs(z-3)=abs(z+4) | | 3(r)=-5r+13 | | 7(x-2)=-9(x+3)+33 | | 2(b-5)=10 | | -4=2(v-6)-8 | | 0=3y^3+4y^2-27y-36 | | 11X+12Y=47434 | | 5*x^3=70000 | | 2x-1=10-x | | 6(X+3)=14x-10 | | 23x+2y=120 | | 7-549347584x+67x=1000007 | | m=3/4xn | | 4ax-2=x+2a | | 4(v+2)+2=18 | | 4(n-16)-19=-19 | | 4x-3=81 | | y=x^2ln(x) | | 7n+20=20+4n | | 166048996/x^2=0 | | 3A+2(A+1)= | | 13-153=5-9 | | 500(3)=-16t^2+175t+500 | | 4a+4=16-a | | h(t)=-16t^2+175t+500 | | 5x+x^2=80 | | x^4-2*x-2=0 |